Next generation selective estrogen receptor degraders in postmenopausal women with advanced-stage hormone receptors-positive, HER2-negative breast cancer - Sharaf, Baha’; Hajahjeh, Abdelrahman; Bani Hani, Hira; Abdel-Razeq, Hikmat (Frontiers in Oncology, 2024)
Breast cancer is the most prevalent malignancy in women, and is characterized by its heterogeneity; exhibiting various subgroups identifiable through molecular biomarkers that also serve as predictive indicators. More than two thirds of breast tumors are classified as luminal with positive hormone receptors (HR), indicating that cancer cells proliferation is promoted by hormones.Endocrine therapies play a vital role in the effective treatment of breast cancer by manipulating the signaling of estrogen receptors (ER), leading to a reduction in cell proliferation and growth rate. Selective estrogen receptor modulators (SERMs), such as tamoxifen and toremifene, function by mimicking blocking estrogen's effects.Aromatase inhibitors (AI), including anastrozole, letrozole and exemestane, suppress estrogen production. On the other hand, selective estrogen receptor degraders (SERDs), like fulvestrant, act by blocking and damaging estrogen receptors. Tamoxifen and AI are widely used both in early-and advanced-stage disease, while fulvestrant is used as a single agent or in combination with other agents like the cyclin-dependent kinase 4 and 6 (CDK4/6) inhibitors (palbociclib, abemaciclib, ribociclib) or alpelisib for advanced-stage disease.Currently, SERDs are recognized as an effective therapeutic approach for the treatment of ER-positive breast cancer, showing proficiency in reducing and blocking ER signaling. This review aims to outline the ongoing development of novel oral SERDs from a practical therapeutic perspective, enhancing our understanding of the mechanisms of action underlying these compounds.